Reduced acrolein detoxification in akr1a1a zebrafish mutants causes impaired insulin receptor signaling and microvascular alterations - Qi, Haozhe; Schmöhl, Felix; Li, Xiaogang; Qian, Xin; Tabler, Christoph Tobias; Bennewitz, Katrin; Sticht, Carsten; Morgenstern, Jakob; Fleming, Thomas; Volk, Nadine; Haußer-Siller, Ingrid; Heidenreich, Elena; et al. (Advanced science, 2021)
Increased acrolein (ACR), a toxic metabolite derived from energy consumption, is associated with diabetes and its complications. However, the molecular mechanisms are mostly unknown, and a suitable animal model with internal increased ACR does not exist for in vivo studying so far. Several enzyme systems are responsible for acrolein detoxification, such as Aldehyde Dehydrogenase (ALDH), Aldo-Keto Reductase (AKR), and Glutathione S-Transferase (GST). To evaluate the function of ACR in glucose homeostasis and diabetes, akr1a1a−/− zebrafish mutants are generated using CRISPR/Cas9 technology. Accumulated endogenous acrolein is confirmed in akr1a1a−/− larvae and livers of adults. Moreover, a series of experiments are performed regarding organic alterations, the glucose homeostasis, transcriptome, and metabolomics in Tg(fli1:EGFP) zebrafish. Akr1a1a−/− larvae display impaired glucose homeostasis and angiogenic retina hyaloid vasculature, which are caused by reduced acrolein detoxification ability and increased internal ACR concentration. The effects of acrolein on hyaloid vasculature can be reversed by acrolein-scavenger l-carnosine treatment. In adult akr1a1a−/− mutants, impaired glucose tolerance accompanied by angiogenic retina vessels and glomerular basement membrane thickening, consistent with an early pathological appearance in diabetic retinopathy and nephropathy, are observed. Thus, the data strongly suggest impaired ACR detoxification and elevated ACR concentration as biomarkers and inducers for diabetes and diabetic complications.